Geometrically uniform trellis codes for noncoherent detection. - Raphaeli, D. (IEEE Transactions on wireless communications)
The definition of geometrically uniform (GU) codes, which exhibit the property of uniform error probability (UEP), had led to the work of finding such codes for the coherent detection with additive white Gaussian noise (AWGN) channel scenario. The extension of this notion for noncoherent detection as UEP for wider channel and decoder condition were referred to as general uniform error (GUE) codes. We consider the problem of finding good GUE codes for noncoherent detection using the independent overlapped observation noncoherent maximum likelihood sequence estimator decoder, for L× MPSK modulation transmitted over AWGN channels. We list good codes for noncoherent decoding. We checked both rotational variant and invariant codes and, due to complexity reduction in the invariant case, show their advantage for noncoherent decoding.